Educational software for stress analysis of thin-walled sections 1 : Isotropic material - Ismail, Nurhuda; Mohamed Ali, Jaafar Syed (2011)
Abstract— An educational software which can aid students in stress analysis of thin-walled open sections has been developed. The software enables students to select different cross-sections which may be subjected to bending, shear or torsional loads and evaluate the stresses on it. Results obtained through this software have been validated against literature. The software has been developed using Visual Basic 6 with graphical user interface (GUI). The software is expected to be a useful tool for effective teaching learning process of courses on thin-walled structures, aircraft structures and advanced mechanics of materials.